Occupational Stress and Its Impact on Work and Work-Life Balance among Nurses in a Large Private Hospital in South India - Adiba MSW; Ravichandran Nair (Institute of Medico-legal Publications Pvt Ltd, 2021)
The job stress is common among all the professions. The nursing profession is combined with stressfulwork environments and heavy workload that are leading to work life imbalance. Stress has been a routineand accepted as part of the nursing profession and there is lack of research on occupational stress in southIndia. The aim of this study is to find out the factors of occupational stress and its impact on work andwork life balance of nursing professionals in a large private hospital in south India. There are many reasonsthat affect work life balance of the nursing professionals. The study is focused on more on factors thatleads to occupational stress. The universe of the study was nursing professionals in a large private hospitalin South India. For this study purpose the researcher is used quantitative study method and descriptiveresearch design. The hospital is having more than one thousand bed capacity and consists of 600 nursingprofessional including permanent and contractual nature of employment. The study sample consists of 60respondents (permanent nurses) including both male and female nursing professional are selected. Simplerandom sampling method is used and collected primary data. The data is collected by using self-administeredquestionnaire. The questionnaires were distributed among in all the wards/units of the hospital. The dataanalysis was done through Microsoft Excel and the inferences were drawn and presented. The findings of thestudy reveal that the heavy workload, long working hours and insufficient staff are the main factors that leadto occupational stress. The stress really affected on their work life balance and nursing professionals werenot able to concentrate on their work which will also lead to other health related problem.